MODEL KEPENGAYOMAN SRI SULTAN HAMENGKU BUWONO X SAAT PANDEMI MELALUI TUTURAN “TIDHA-TIDHA” DALAM SAPA ARUH - Marcelinus Justian Priambodo (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2021)
This research aims to describeconcept from 'tidha-tidha’ and analyze the affect of the concept of 'tidha-tidha' made by Sri Sultan Hamengku Buwono X with the conceptual metaphor of the coronavirus in the society of Yogyakarta. Data in this research is internal because it is only based on the reading of Serat Kalatidha and the transcript of Sri Sultan Hamengku Buwono X's speech. This research method uses the theory ofconceptual errors in cognitive linguistic. Sri Sultan Hamengku Buwono X interprets ‘tidha-tidha’ as contemplation with ourselves, others, and God. This new disaster has made people aware of the importanceof health as a form of gratitude that must be attempted. The results reveal that perspective and frame affect the meaning of 'tidha-tidha’ made by Sri Sultan Hamengku Buwono X. The creation of this meaning has three functions consisting representative, directive, and declaration to change the conceptual metaphor of society. In his role as governor, Sri Hamengku Buwono X must change the way og communication as the leadership model and at the same time to respond that new disaster. The leadership model can be seen from the directions and instructions in the speech that are easy to understand through the intentional conceptual errors.Penelitian ini bertujuan untuk mendeskripsikan makna ‘tidha-tidha’ dan menganalisis pengaruh makna ‘tidha-tidha’ ciptaan Sri Sultan Hamengku Buwono X dengan metafora konseptual pandemi corona masyarakat DIY. Data penelitian bersifat data internal karena hanya berdasarkan pembacaan Serat Kalatidha dan hasil transkrip pidato Sri Sultan Hamengku Buwono X. Metode penelitian ini menggunakan pendekatan deskriptif analisis yang menggunakan teori erata konseptual linguistik kognitif. Hasil penelitian menunjukkan bahwa perspektif dan frame dan memengaruhi pembentukan makna ‘tidha-tidha’ ciptaan Sri Sultan Hamengku Buwono X. Sri Sultan Hamengku Buwono X memaknai ‘tidha-tidha’ sebagai kontemplasi dengan diri sendiri, sesama, dan Sang Pencipta.Bencana baru ini menyadarkan manusia pentingnya kesehatan sebagai rasa syukur yang harus diusahakan. Penciptaan makna ini memiliki tiga fungsi yaitu representatif, direktif, dan deklarasi dalam upaya mengubah metafora konseptual masyarakat. Dalam perannya sebagai gubernur, Sri Sultan Hamengku Buwono X harus mengubah cara komunikasisebagai bentuk pengayoman sekaligus menyikapi keadaan baru tersebut. Model pengayoman terlihat dari arahan dan petunjuk dalam pidato yang mudah dipahami melalui erata konseptual kesengajaan.